Controls on fluid movement in crustal lithologies: evidence from zircon in metaconglomerates from Shetland. Issue 3 (1st April 2016) - Dempster, T. J.; Macdonald, F.
Abstract: An investigation of the morphology of zircon in clasts and matrix of a greenschist facies metaconglomerate from Shetland has revealed a history of alteration of radiation‐damaged grains, partial dissolution and growth of new zircon. These processes are linked to the generation of chemically modified dark backscattered electron (BSE) zircon that is spatially related to fractures generated during radiation damage; embayments and rounding of zircon margins; and late overgrowths of original grains. These late modifications of zircon are all linked to the presence of fluids and so zircon morphology is used to track fluid behaviour in different lithologies in the metaconglomerate. Alteration is unrelated to clast margins and radically different in various clast types. This reflects a difference in permeability and suggests that deformation strongly controls fluid influx into quartzite, whereas zircon alteration in granite is associated with a restricted permeability reflecting the more limited response to deformation events. Abstract : Movement of low‐temperature fluids through rocks causes alteration of zircon resulting in chemical modification, dissolution and new growth. This investigation of zircon textures in different clast types and matrix in a metamorphosed conglomerate reveals different responses of zircon linked to different permeability controls. Fluid influx in these metamorphic rocks is shown to primarily occur along discrete pathways controlled by the response of quartz, plagioclase and phyllosilicates to deformation.